2008
DOI: 10.1016/s0091-679x(08)00610-9
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 10 Infrared and Raman Microscopy in Cell Biology

Abstract: This chapter presents novel microscopic methods to monitor cell biological processes of live or fixed cells without the use of any dye, stains, or other contrast agent. These methods are based on spectral techniques that detect inherent spectroscopic properties of biochemical constituents of cells, or parts thereof. Two different modalities have been developed for this task. One of them is infrared micro-spectroscopy, in which an average snapshot of a cell's biochemical composition is collected at a spatial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 31 publications
2
119
0
5
Order By: Relevance
“…Figure 2 Raman spectra of selected cellular components. Section 3.2) in Raman microscopy is similar to that of confocal fluorescence microscopy [22].…”
Section: Introductionmentioning
confidence: 89%
“…Figure 2 Raman spectra of selected cellular components. Section 3.2) in Raman microscopy is similar to that of confocal fluorescence microscopy [22].…”
Section: Introductionmentioning
confidence: 89%
“…It is possible to identify prominent spectral peaks in characteristic spectral regions. These features arise from the molecular vibration of components of the oocyte cortex such as lipids and proteins [27]. deformation of the proteins and lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Raman offers the advantage of acquiring information regarding the biochemical constituents of the sample and their spatial distribution without labelling, on both fixed and unfixed cells. This technique has been, widely, used to study the biological changes of various cellular components during cell cycle progression, apoptosis, and response to stress [27]. On the other hand, studies focused on female gamete are restricted to a few works [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Two opposing interpretations have been used to discuss intensity changes of peaks during treatments. The first interpretation states that as the intensity of Raman peaks depends linearly on the concentration of molecules in a sample, a lower concentration will imply that the associated Raman peak decreases in intensity [13]. The second interpretation suggested that when molecules denature or lose their form and function the intensity of some Raman peaks will increase [7].…”
Section: Raman Spectra Of Vehicle Treated (Dmso) Cellsmentioning
confidence: 99%